DETERMINANTS OF CYBER RISK DISCLOSURE: REVIEW ARTICLE - Samir Emad Shaaban; Ahmed Fadhil Saleh; Mohamed Ahmed Dheyab (Scholars Digest Publishing, 2024)
Disclosure of cyber risks is predominantly important, as the importance of cyber risk disclosure decisions has increased due to the large number of attacks and breaches that have affected companies' data and information. This analysis aimed to contribute to the scientific discussion to clarify the challenges facing companies in disclosing cyber risks due to rapid developments in information technology by reviewing many studies that dealt with cyber risk disclosure and the factors that affect it. Earlier studies and articles from various local, Arab, or foreign magazines were reviewed to reach the basic determinants and factors that affect this disclosure. The study reached a group of results, which were that relying on modern information technology in decision-making due to interconnected systems that contain a large set of data and information is one of the challenges that companies may face because they are more exposed to potential or actual cyber risks and the extent of the possibility of confronting and addressing these risks, in addition to another set of challenges facing companies when disclosing cyber risks, represented by previous cyber incidents, cyber security breaches, and corporate governance (board of directors size and independence, gender diversity, institutional ownership, and Foreign ownership) and the size and growth of the company, the type of activity, and the technology committee.
Keywords: Cyber risk, Cyber Security, cyber risk disclosure, determinants of cyber risk disclosure.